Maritime and offshore structure maintenance proceedings of the Second International Conference on the Maintenance of Maritime and Offshore Structures, organized by the Institution of Civil Engineers and held in London on 19-20 February 1986. (Thomas Telford, 1986)
These papers deal with issues concerning maritime and offshore structure maintenance, from the challenge of port maintenance in developing countries to major repairs to a loading quay and approach bridge. An outline is also given of guidelines for inspection and maintenance of marine facilities.